Delusion-proneness predicts COVID-19 vaccination behavior - Acar, Kasim; Karagiannidou, Ariadni; Olsson, Andreas; van Prooijen, Jan-Willem; Balter, Leonie J. T.; Axelsson, John; Ingvar, Martin; Lebedev, Alexander V.; Petrovic, Predrag (Frontiers in Psychiatry, 2024)
IntroductionVaccination-related conspiracy ideation is related to reduced compliance with public health advice globally. Such beliefs have previously been linked to the delusion-proneness trait. However, it is not known how this extends to getting vaccinated.MethodsHere, we examined how delusion-proneness, as assessed by Peters et al. Delusions Inventory (PDI), is associated with COVID-19 vaccination in a sample of 273 subjects. We also examined whether delusion-proneness predicted the time to get vaccinated, after the vaccine became available.ResultsUnvaccinated subjects were more delusion-prone than vaccinated subjects (W=2225.5, p<0.001, effect-size=0.27). Among vaccinated subjects, higher delusion-proneness was related to longer time to get vaccinated (rs=0.27, p<0.001). These effects remained after adjusting for anxiety, ADHD, and ASD (Autism Spectrum Disorder) traits as well as for psychiatric diagnoses and sex. Path analyses indicated that the effect of delusion-proneness on vaccination rate was strongly mediated through COVID-19 conspiracy ideation, suggesting that delusion prone individuals first develop specific delusion-like ideas regarding vaccination, which then delays vaccination. An exploratory analysis of written text by subjects instructed to explain why they had vaccinated or not, revealed a difference in reasoning between the groups. Unvaccinated individuals were primarily motivated by concerns about personal safety and potential side effects, while vaccinated individuals stated a desire to protect themselves and others as the primary reasons to get vaccinated. DiscussionOur results suggest that delusion-proneness is a key factor for attaining conspiracy beliefs, at least in relation to COVID-19 pandemic, and associated with lower vaccination rates as well as longer time to get vaccinated.